2020
DOI: 10.26714/medart.2.1.2020.17-20
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Jenis Kelamin dan Riwayat Asma dengan Rinitis Alergi pada Pelajar SMP Muhammadiyah 3 Palembang

Abstract: Latar Belakang: Rinitis alergi adalah suatu penyakit pada hidung yang ditimbulkan oleh reaksi inflamasi mpada mukosa hidung dengan perantara immunoglobulin E. Prevalensi rinitis alergi di dunia telah meningkat termasuk di Indonesia yang kini telah mencapai 1,5-12.4% dan cenderung mengalami peningkatan setiap tahunnya. Penelitian ini bertujuan untuk mencari prevalensi rinitis alergi dan hubungan antara jenis kelamin dan riwayat asma dengan kejadian rinitis alergi pada siswa sekolah di Palembang. Metode: Penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…This situation will stimulate the production of inflammatory mediators such as histamine and leukotrienes and cytokines such as IL-4 and IL-5. 5,22 Our study found there was a difference between the quality of life between students with allergic rhinitis and students who did not suffer from allergic rhinitis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This situation will stimulate the production of inflammatory mediators such as histamine and leukotrienes and cytokines such as IL-4 and IL-5. 5,22 Our study found there was a difference between the quality of life between students with allergic rhinitis and students who did not suffer from allergic rhinitis.…”
Section: Discussionmentioning
confidence: 65%
“…The hormones estrogen and progesterone in women have an inflammatory effect, whereas testosterone in men has an anti-inflammatory effect. 2,5 Based on the age distribution, the highest number of allergic rhinitis was at the age of 21 years as many as 111 (52%). This is in accordance with the theory stated that allergic rhinitis sufferers were in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Penelitian serupa di daerah lain pada pelajar sekolah dasar (SD) dengan rentang usia 10-12 tahun di Bandar Lampung, sebanyak 85 dari 901 pelajar yang diteliti memiliki rinitis alergi disertai dengan asma. 13 Berdasarkan latar belakang diatas, penelitian ini dilakukan dengan tujuan untuk mengetahui banyaknya frekuensi riwayat asma beserta karakteristiknya pada pasien rinitis alergi.…”
Section: Pendahuluanunclassified